Left‐to‐right shunt reduction with intra‐aortic balloon pump in postmyocardial infarction ventricular septal defect. Issue 4 (17th April 2012) - Testuz, Ariane; Roffi, Marco; Bonvini, Robert Francis
<x xml:space="preserve">Abstract</x> This case aims to describe the hemodynamic effects of intra‐aortic balloon pump (IABP) in patients with ventricular septal defect (VSD) complicating myocardial infarction (MI). A 79‐year‐old man with no previous cardiovascular history presented to the emergency department with subacute inferior myocardial infarction associated with mild signs of systemic hypoperfusion. A transthoracic echocardiography revealed a large akinesia of the left ventricular inferior wall with preserved global left ventricular ejection fraction, as well as a large VSD in the midinferior portion of the interventricular septum. Coronary angiography showed an occlusion of the mid portion of a dominant circumflex coronary artery. The invasive hemodynamic evaluation showed a sizable left‐to‐right shunt (Qp/Qs = 3.1). Activation of the IABP led to an immediate reduction of the shunt (Qp/Qs = 2.4 = 22% reduction), an increase in systemic cardiac output (from 2.1 L/min to 2.4 L/min = +12%) and a decrease in the systemic vascular resistances (from 2240 to 1920 dyne‐sec/cm5 = 15% reduction). In patients with post‐MI VSD, placement of IABP leads to an immediate reduction in left‐to‐right shunt and as a consequence to an increase in systemic cardiac output, which may allow hemodynamic stabilization of the patient prior to surgical VSD closure. © 2012 Wiley Periodicals, Inc.